KONSEP PENDIDIKAN DALAM ISLAM PERSPEKTIF AHMAD TAFSIR - Arief Rifkiawan Hamzah (AT-TAJDID, 2017)
The purpose this research is to identify and explain the nature of man according Ahmad Tafsir and his views about the Islamic education. Knowing human nature is the first step that must be known in the implementation of education, because knowing that the concepts of Islamic education can be formulated in accordance with the nature of man. But many Islamic educational institution hasn’t give a attention about that, financial, and implement the Islamic educational concept, making it less able to develop the institution. Through the idea of Ahmad Tafsir is expected to contribute to both improve the quality of Islamic education institution. This research is librabry research with documentation research techniques. The result from this study is that the man is a servant of God who made the caliph of God Wich can be guided through the educational institution to increase their potential.Keyword: Concept, Islamic Education, Ahmad Tafsir